PENGARUH KEBIJAKAN PENGAMPUNAN PAJAK TERHADAP PERMOHONAN PENGAJUAN KEBERATAN DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK - Adiman, Sumardi (Universitas Pembangunan Panca Budi, 2024)
Tax Amnesty policy is one of the important policies in order to optimize the national banking business. It is hoped that this policy will provide benefits not only to the national economy but also to the government and taxpayers themselves. In addition, this policy also has the potential to add to the national economy which can then be utilized for domestic economic activities. Tax amnesty is an opportunity given in a short time to taxpayers to pay a sum of money as an exemption from liability (including interest and penalties) in connection with the previous tax year without any worries to be prosecuted. With the existence of tax amnesty is expected to produce tax revenue that has not been paid or underpaid, besides that this is done to improve taxpayer compliance in paying taxes. The increase in compliance is also a result of the increasingly effective oversight of taxpayers, because the information on the taxpayer's wealth list will be more accurate as well. Banks as credit suppliers can become intermediaries for taxpayers who take part in this program. because every taxpayer who follows the tax amnesty program, is obliged to pay a sum of money as a ransom to the state. With this ransom, for taxpayers who lack funds in ransom payments, can apply for credit to the bank. With the existence of the credit is expected to provide convenience for taxpayers to pay ransoms for the tax amnesty program so that there are no more reasons for taxpayers to pay in arrears.